Case Report: Whole Exome Sequencing Revealed Two Novel Mutations of PIEZO1 Implicated in Nonimmune Hydrops Fetalis - Chen, Yuan; Jiang, Ying; Chen, Bangwu; Qian, Yeqing; Liu, Jiao; Yang, Mengmeng; Zhao, Baihui; Luo, Qiong (Frontiers in Genetics, 2021)
Nonimmune hydrops fetalis (NIHF) is a serious and complex fetal condition. Prenatal diagnosis of NIHF is not difficult by ultrasound. However, determining the underlying etiology of NIHF remains a challenge, which is essential for prenatal counselling. We extracted DNA from a proband prenatally diagnosed unexplained NIHF. Trio-whole exome sequencing (WES) was performed to filter candidate causative variants. Two gene mutations are identified as a compound heterozygous state in the proband. Both variants located on the PIEZO1 gene: c.3895C>T, a missense mutation in exon 27 paternally inherited; c.4030_4032del, a maternally inherited in-frame deletion in exon 28. Both variants were firstly reported to be related with NIHF. PIEZO1 gene mutations can lead to a autosomal recessive congenital lymphatic dysplasia which can present as NIHF and partially or complete resolution postnatally. In conclusion, WES can aid in the elucidation of genetic cause of NIHF and has a positive effect on the assessment of prognosis.